Synthesis of magnetic Fe3O4-HKUST-1 nanocomposites for azo dye adsorption - Zhiyu Ma; Chenhui Liu; C. Srinivasakannan; Lingbo Li; Yongli Wang (Arabian Journal of Chemistry, 2023)
The magnetic Fe3O4-HKUST-1 nanocomposites were synthesized using a simple and green hydrothermal technique, utilizing Fe3O4 and the chemically stable metal–organic framework HKUST-1. The Fe3O4-HKUST-1 nanocomposites were synthesized with a varied proportion of Fe3O4 and subjected to advanced characterization, which included XRD, IR, BET, TG, SEM, TEM, EDS, and VSM. The magnetic nanocomposite 0.4 Fe3O4-HKUST-1 (FH4) had a rough surface with spherical morphology and a good proportion of micro and mesopores. The magnetic nanocomposite had a mean pore size of 2.58 nm, with pore volume of 0.35 cm3/g, having excellent magnetic saturation performance (26.39 emu/g). The adsorption isotherm and adsorption kinetics of magnetic nanocomposites on azo dye neutral red (NR) wastewater were assessed in detail. In contrast to the Freundlich model, the Langmuir model better described the adsorption isotherms, while the pseudo-second-order kinetic model better captured the adsorption kinetics. The FH4 magnetic nanocomposite was the most effective adsorbent with the highest adsorption capacity for NR separation.